Language change - Trask, R. L. (Robert Lawrence) 1944- (Language workbooks, 1994)
In Language Change , R. L. Trask uses data from English and other languages to introduce the concepts central to language change. This book covers the most frequent types of language change and how languages are born and die uses data-based exercises to show how languages change looks at other key areas such as attitudes to language change, and the consequences of changing language